The Effect Of The Development Of Electricity, Sanitation, Health, And Education Infrastructure On District/City Poverty In Lampung Province - Fajar Aditya Nugraha; Asih Murwiati (Cita konsultindo, 2024)
This study aims to analyze how infrastructure, which consists of electricity, sanitation, health and education, affects the poverty rate in 15 regencies/cities in Lampung Province. This study uses quantitative methods in the form of multiple regression analysis with panel data. The type of data used is secondary data from 15 districts / cities in Lampung Province for the period 2018-2022 obtained from the Central Bureau of Statistics (BPS) which includes: percentage of poor people, percentage of households that have access to PLN electricity, percentage of households that have access to proper sanitation, average years of schooling, and life expectancy. The results of the analysis using the selected fixed effect model approach show that sanitation, health, and education have a significant negative effect on the poverty rate. This means that an increase in each infrastructure has an impact on decreasing the percentage of poor people in districts/municipalities in Lampung Province. Meanwhile, the electricity variable has a positive and insignificant effect on poverty. This means that an increase in the electricity variable has no impact on reducing poverty in districts/municipalities in Lampung Province.